2017
DOI: 10.1063/1.4979064
|View full text |Cite
|
Sign up to set email alerts
|

Local bifurcation of electrohydrodynamic waves on a conducting fluid

Abstract: We are concerned with progressive waves propagating on a two-dimensional conducting fluid when a uniform electric field is applied in the direction perpendicular to the undisturbed free surface. The competing effects of gravity, surface tension, and electrically induced forces are investigated using both analytical and numerical techniques for an inviscid and incompressible fluid flowing irrotationally. We simplify the full Euler equations by expanding and truncating the Dirichlet-Neumann operators in the Hami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…More than that, Barannyk et al showed in [15] that the tangential electric field can even suppress the RayleighTaylor instability in some situations. On the contrary, it can be deduced from the work by Gleeson et al [16], Papageorgiou et al [21], Lin et al [2], and Wang [8] that the normal electric field has a destabilizing effect on the interface. N. M. Zubarev and O. V. Zubareva [10,20] and Tao and Guo [22] considered the electrified gas-fluid or vacuumfluid interface so that they can make the assumption that the permittivity of the fluid was much larger compared to that of gas (the permittivities for pure water and air are 80 and 1, resp.).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…More than that, Barannyk et al showed in [15] that the tangential electric field can even suppress the RayleighTaylor instability in some situations. On the contrary, it can be deduced from the work by Gleeson et al [16], Papageorgiou et al [21], Lin et al [2], and Wang [8] that the normal electric field has a destabilizing effect on the interface. N. M. Zubarev and O. V. Zubareva [10,20] and Tao and Guo [22] considered the electrified gas-fluid or vacuumfluid interface so that they can make the assumption that the permittivity of the fluid was much larger compared to that of gas (the permittivities for pure water and air are 80 and 1, resp.).…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial electrohydrodynamic waves have many important applications in mechanical, chemical, and electrical industries, such as electrospray ionization, cooling systems, coating process, and electrowetting (see [1][2][3][4][5][6][7][8][9][10] and the references therein). The electric stresses have great impact on electrified free surfaces or interfaces, which can not only modify wave patterns but also change stability characteristics of the system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such instabilities have been speculated to lead to the formation of rogue waves [34,41], or the decrease in the frequency of the monochromatic wave [28,7,39]. However, even when such waves are stable to an instability like this, they can undergo different morphologies and generate structures such as dark solitary waves [32,24,30], whose mechanism for formation remains unclear. Therefore, even such a heavily studied problem has a wealth of dynamics we have yet to understand.…”
Section: Introductionmentioning
confidence: 99%